Tau: The Center of a Signaling Nexus in Alzheimer's Disease - Khan, Shahzad S.; Bloom, George S. (Frontiers in Neuroscience, 2016)
Tau is a microtubule-associated protein whose misfolding, hyper-phosphorylation, loss of normal function and toxic gain of function are linked to several neurodegenerative disorders, including Alzheimer’s disease (AD). This review discusses the role of tau in amyloid-β (Aβ) induced toxicity in AD. The consequences of tau dysfunction, starting from the axon and concluding at somadendritic compartments, will be highlighted.